Syncope and paroxysmal atrioventricular block - Milena Aste (Journal of Arrhythmia, 2017)
Current literature reveals three types of paroxysmal atrioventricular block (AVB) that can cause syncope:Intrinsic paroxysmal atrioventricular block is due to an intrinsic disease of the AV conduction system; this type of âcardiac syncopeâ is also called Stokes-Adams attack;Extrinsic vagal paroxysmal atrioventricular block is linked to the effect of the parasympathetic nervous system on cardiac conduction and is one of the mechanisms involved in âreflex syncope.âExtrinsic idiopathic paroxysmal atrioventricular block is associated with low levels of endogenous adenosine and is supposed to be one of the mechanisms involved in âlow-adenosine syncope.âThese three types of paroxysmal AVB present different clinical and electrocardiographic features. Additionally, the efficacy of cardiac pacing and theophylline therapy to prevent syncopal recurrences is also different for these three types of AVB. Keywords: Paroxysmal atrioventricular block, Syncope, Adenosine, Theophylline, Idiopathic atrioventricular block